Super-spreading social events for COVID-19 transmission: evidence from the investigation of six early clusters in Bahrain - Alsayyad, Adel; Chlif, Sadok; Mohamed, Afaf; Habbash, Fatema; Ayoob, Zahra; Almarabheh, Amer; Al Sayed, Kubra; Alsaleh, Aseel; Alhajeri, Maryam; Alzayani, Salman; Abu Alfatah, Najat; Ahmed, Jamil; et al. (Frontiers in Public Health, 2023)
Pairs of "infector-infectee" allowed to map the clusters and to estimate the incubation period, serial interval as well as the secondary attack rate. The chi-square test with p value computed by Monte Carlo test measured associations between categorical variables. Statistical analysis was performed using R Software and "data.tree, tidyverse" libraries.From 9 April to 27 June 2020, we investigated 596 individuals suspected for COVID-19 of whom 127 positive cases, confirmed by PCR and linked in six clusters. The mean age is 30.34 years (S.D. = 17.84 years). The male to female ratio is 0.87 (276/318) and most of contacts are of Bahraini citizenship (511/591= 86.5%). Exposure occurs within the family in 74.3% (411/553) and 18.9% of clusters' cases were symptomatic (23/122 = 18.9%). Mapped clusters and generations increased after 24 May 2020 corresponding to "Aid El-Fitr". The mean incubation period was 4 days and the mean serial interval ranged 3 to 3.31 days. The secondary attack rate was 0.21 (95% C.I.) = [0.17-0.24].COVID-19 transmission amplified due to the high mixing of families during "Aid El Fitr" and "Ramadhan", generating important clusters. Estimated serial interval and incubation period support asymptomatic transmission.